Anxiety and Cognition in Cre- Collagen Type II Sirt1 K/O Male Mice - Shtaif, Biana; Hornfeld, Shay Henry; Yackobovitch-Gavan, Michal; Phillip, Moshe; Gat-Yablonski, Galia (Frontiers in Endocrinology, 2021)
Introduction: Using transgenic collagen type II-specific Sirt1 knockout (CKO) mice we studied the role of Sirt1 in nutritional induced catch up growth (CUG) and we found that these mice have less organized growth plate and reduced efficiency of CUG. In addition, we noted that they weigh more than control (CTL) mice. Studying the reason for the increased weigh, we found differences in activity and brain function. Methods: Several tests for behavior and activity were used: open field; elevated plus maze, Morris water maze, and home cage running wheels. The level of Glu- osteocalcin, known to connect bone and brain function, was measured by Elisa; brain Sirt1 was analyzed on western blot. Results: We found that CKO mice had increased anxiety, with less spatial memory and learning capabilities and reduced activity in their home cages. No significant differences were found between CKO and CTL mice in Glu- osteocalcin levels; nor in the level of brain SIRT1. Discussion/Conclusion: Using transgenic collagen type II-specific Sirt1 knockout (CKO) mice we found a close connection between linear growth and brain function. Using a collagen type II derived system we affected a central regulatory mechanism leading to hypo activity, increased anxiety, and slower learning, without affecting circadian period. As children with idiopathic short stature are more likely to have lower IQ, with substantial deficits in working memory than healthy controls, the results of the current study suggest that SIRT1 may be the underlying factor connecting growth and brain function.